2014
DOI: 10.1016/j.jfa.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Basic sequences and spaceability in p spaces

Abstract: Abstract. Let X be a sequence space and denote by Z(X) the subset of X formed by sequences having only a finite number of zero coordinates. We study algebraic properties of Z(X) and show ( In addition to this, we also give a thorough analysis of the existing algebraic structures within the set X \ Z(X) and its algebraic genericity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…Many more pathologies of this kind can be found in the excellent monograph [59]. See also [2,6,20,41,48,59,71,73] for a long list of pathologies enjoyed by continuous and differentiable functions in R R .…”
Section: 22mentioning
confidence: 99%
“…Many more pathologies of this kind can be found in the excellent monograph [59]. See also [2,6,20,41,48,59,71,73] for a long list of pathologies enjoyed by continuous and differentiable functions in R R .…”
Section: 22mentioning
confidence: 99%
“…A thorough description of the most relevant lineability problems and other related topics can be found in the monograph [4] or in the expository paper [5]. The interested reader may also consult the references [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…After these definitions were introduced by Aron, Gurariy and Seoane-Sepúlveda in [1], many authors showed that many non-linear special sets can often have these properties. See, for instance, the recent works [2][3][4][5][6][7][8], just to cite some. However, before the publication of [1] some authors already found large linear structures enjoying special properties even though they did not explicitly used terms like lineability or spaceability (see [9,10]).…”
Section: Introductionmentioning
confidence: 99%